5 Assessing the role of extracellular vesicles in renin-angiotensin system signalling incardiomyocyte hypertrophy. (1st April 1997) - Downie, Laura S; Nather, Katrin; Work, Lorraine M; Nicklin, Stuart A
Abstract : Introduction: The classical Renin-Angiotensin System has been implicated in cardiovascular remodelling including cardiac hypertrophy while a counter-regulatory axis of the RAS has been shown to have cardioprotective effects against hypertrophy. Here, we show the characterisation of cardiac-derived extracellular vesicles (EVs) from two different cardiac cell types, neonatal rat cardiac fibroblasts (NRCF) and H9c2 cardiomyocytes. We suggest that these EVs may be harnessed for delivery of peptides involved in RAS signalling further leading to either cardioprotective or deleterious effects. Methods: EVs were isolated from NRCF cell or H9c2 cardiomyocyte conditioned media via differential centrifugation/ultracentrifugation and concentration and size was verified by BCA, nanosight and transmission electron microscopy (TEM). H9c2 cardiomyocytes were left untreated (control) or treated with 1 µM AngII or 1 µM Ang-(1-7) soluble peptide for 48 hours. EVs were isolated and placed onto recipient H9c2 cardiomyocytes for 96 hours, phalloidin stained cells were then imaged by confocal microscopy and sized on Image J for analysis of hypertrophy. Results: EVs isolated from NRCF cells are larger and released at higher concentrations than those isolated from H9c2 cardiomyocytes (NRCF EVs 200 nm size, 3.5 × 10 8 particles/ml vs. H9c2 EVs 100 nm size, 2.5 × 10 8 particles/ml). EVs isolated from 1 µM AngII treated H9c2 cardiomyocytes significantly increased cell area of recipient H9c2 cardiomyocytes (control EV treated 3291.1±90.1 µm 2 vs AngII EV treated 5252.3±125.4 µm 2, p<0.001). EVs isolated from 1 µM Ang-(1-7) treated H9c2 cardiomyocytes significantly reduced AngII peptide induced increase in cell area in a dose dependent manner in recipient H9c2 cardiomyocytes (100 nM AngII+Control EVs 5566.3±139.0 µm 2 vs 100 nM AngII+Ang-(1-7) EVs 4212.7±132.1 µm 2, p<0.001). Summary/conclusions: Collectively these data suggest that there are distinct sub-populations of EVs released that differ between NRCF cells and H9c2 cardiomyocytes. We have shown that H9c2-derived EVs can elicit deleterious or cardioprotective effects on recipient H9c2 cardiomyocytes depending on the condition of the parental cells.